Blastocyst Development in a Single Medium Compared to Sequential Media: A Prospective Study With Sibling Oocytes. (September 2017) - Sfontouris, Ioannis A.; Kolibianakis, Efstratios M.; Lainas, George T.; Petsas, George K.; Tarlatzis, Basil C.; Lainas, Trifon G.
The aim of the present study was to compare blastocyst formation rates after embryo culture in a single medium (Global) as compared to sequential media (ISM1/BlastAssist). In this prospective trial with sibling oocytes, 542 metaphase II (ΜΙΙ) oocytes from 31 women were randomly and equally divided to be fertilized and cultured to the blastocyst stage in either sequential media (ISM1/BlastAssist; n = 271 MII oocytes) or a single medium (Global; n = 271 MII oocytes). In both groups, embryos were cultured in an interrupted fashion with media changes on day 3. Embryo transfer was performed on day 5. Blastocyst formation rates on day 5 (61.7% ± 19.9% vs 37.0% ± 25.5%, P < .001) were significantly higher following culture in Global as compared to ISM1/BlastAssist, respectively. Fertilization rates, cleavage rates, and percentage of good quality embryos on day 3 were similar between Global and ISM1/BlastAssist, respectively. The percentages of good quality blastocysts (63.0% ± 24.8% vs 32.1% ± 37.2%, P < .001), blastocysts selected for transfer (27.8% ± 19.2% vs 11.1% ± 14.4%, P = .005), and utilization rates (62.5% ± 24.8% vs 39.0% ± 25.2%, P < .001) were significantly higher in Global as compared to ISM1/BlastAssist, respectively. In conclusion, culture in Global was associated with higher blastocyst formation rates compared to ISM1/BlastAssist, suggesting that the single medium may provide better support to the developing embryo.